2006
DOI: 10.1007/s00299-006-0200-z
|View full text |Cite
|
Sign up to set email alerts
|

Gynogenic plant regeneration from unpollinated flower explants of Eragrostis tef (Zuccagni) Trotter

Abstract: Tef [Eragrostis tef (Zucc.) Trotter] is the most important cereal in Ethiopia. In its wild relative E. mexicana, regeneration of six green plants resulted from culture of 121 non-pollinated immature pistils. In the allotetraploid crop species tef, however, only callus and root formation was obtained by this method. By contrast, immature spikelets and panicle segments of E. tef proved amenable to gynogenic plant regeneration. Upon step-wise optimization of the protocol, efficient plant formation was achieved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…However, this effect is likely to be genotype-dependent since we did not observe any beneficial effect of thermal shock pretreatment on the ELS formation of the five Thai cultivars. Insensitivity to thermal shock pretreatment on several plants has also been reported (Metwally et al, 1998;Gugsa et al, 2006). It was shown that squash ovules without cold pretreatment at 4°C produced a better embryogenic response than the ones treated at 4°C for 2, 4 or 8 days (Metwally et al, 1998).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, this effect is likely to be genotype-dependent since we did not observe any beneficial effect of thermal shock pretreatment on the ELS formation of the five Thai cultivars. Insensitivity to thermal shock pretreatment on several plants has also been reported (Metwally et al, 1998;Gugsa et al, 2006). It was shown that squash ovules without cold pretreatment at 4°C produced a better embryogenic response than the ones treated at 4°C for 2, 4 or 8 days (Metwally et al, 1998).…”
Section: Discussionmentioning
confidence: 84%
“…It was shown that squash ovules without cold pretreatment at 4°C produced a better embryogenic response than the ones treated at 4°C for 2, 4 or 8 days (Metwally et al, 1998). Similarly, pretreatment at 4°C for up to 9 days or at 32°C for 1 day did not improve gynogenic development of tef pistil culture (Gugsa et al, 2006). ELS and callus formation potentials varied significantly when using different induction media.…”
Section: Discussionmentioning
confidence: 97%
“…Variation from gynogenically derived tef (Eragrostis teff (Zuccagni)), an important cereal crop of Ethiopia, was found for plant height, panicle length, culm thickness, seed size, and maturity (Gugsa and Loerz, 2013;Gugsa et al, 2006). Likewise, several DH regenerants obtained after anther culture (or microspores) showed large variation for improved agronomic characteristics in rice (Ying et al, 1996;Yoshida et al, 1998), while dihaploid plants in potato originating through gametoclonal variation during androgenic dihaploidization were genetically most distinct from their tetraploid anther-derived sibs as well as anther donor (Sarkar et al, 2010).…”
Section: Gametoclonal Variationmentioning
confidence: 99%
“…This technique is the female equivalent of the process described in the paragraph above, and has been applied to species including sugar beet [55,56], onion [57,58], squash [59], gerbera [60], rice [61], maize [62], niger [63] and tea [64]. Ovules have also been used as a transformation target [39].…”
Section: Ovule Culturementioning
confidence: 99%